Flood risk prediction and modeling in Bauchi: leveraging machine learning models and explainable AI for urban resilience - Kafi, Kamil Muhammad; Ponrahono, Zakiah; Ash’aari, Zulfa Hanan; Barau, Aliyu Salisu (Elsevier BV, 2025)
Floods are amongst the most destructive weather and climate-related disasters, causing significant loss of life and property globally. Accurate flood risk prediction is crucial for improving disaster resilience and urban planning.